Pharmacological Antagonism of T-Type Calcium Channels Constrains Rebound Burst Firing in Two Distinct Subpopulations of GABA Neurons in the Rat Ventral Tegmental Area: Implications for α-Lipoic Acid - Woodward, Taylor Joel; Tesic, Vesna; Stamenic, Tamara Timic; Jevtovic-Todorovic, Vesna; Todorovic, Slobodan M. (Frontiers in Pharmacology, 2019)
The ventral tegmental area (VTA) is a midbrain region highly involved in motivation and reward. A large body of work has investigated synaptic plasticity and ion channel excitability in this area, which has strong implication in drug abuse. We recently provided electrophysiological and pharmacological evidence that the CaV3.1 isoform of T-type voltage-gated calcium channels contributes to the excitability of VTA dopamine (DA) neurons. However, the role of T-channels in excitability of VTA gamma-amino-butyric acid (GABA) neurons remained unaddressed. Here, with a population study of rat VTA GABA neurons, we provide evidence that T-channels contribute to rebound spiking activity in two phenotypically distinct subpopulations of GABAergic neurons, each with differing electrophysiological characteristics. Additionally, we provide the first study to investigate the effect of α-lipoic acid (ALA) on ion channels in mesolimbic reward circuitry. Taken together, our population study and pharmacology experiments implicate T-channels as a target for therapies aimed at tempering VTA and mesolimbic circuit excitability.